Ցլի եւ Օձավիշապի աստղային եղանակային կոդերը հին հայոց աշխարհայեացքում - Մարտոյեան, Գագիկ (տպ. Atlas)
Basing their work on Balto-Slavic Bilin epic tales, prominent Russian philologists V.V. Ivanov and V.VI. Toporov reconstructed the myth of the duel between the bullshaped God of Thunder and the Serpent. In the battle the Serpent is defeated and disappears into underground waters. Ivanov and Toporov claim that in Middle Eastern versions of this myth, the winner may be the Serpent. Besides, the Sun may also prevail over the Serpent. Armenian beliefs have preserved two types of snake images. One of them is the horned Zagrosh, which is defeated by the bull Tavros. In the other version, the Snake fights the Ox and eats it. Armenian beliefs have two types of oxen: Black and Red. During the spring of the Palm Sunday holiday, in the Armenian tradition Black Ox is promised a rope around its neck that will choke it, while the Red Ox is promised a rope with a button. In the epic poem of Daredevils of Sasun, the White devil (symbol of winter), sits on the Black Ox and, moving around the world, ruins it. The Elder Mher (Mithra, the sun) kills them both, thereby driving away winter and bringing the spring and the New Year.
Keywords: Ազգագրութիւն